Detection and characterization of potentially pathogenic Aeromonas sobria isolated from fish Hypophthalmichthys molitrix (Cypriniformes: Cyprinidae). (February 2016) - Dar, Gowhar H.; Dar, Shoaib A.; Kamili, Azra N.; Chishti, Mohammad Z.; Ahmad, Fayaz
Abstract: The current study focuses on the detection and characterization of potentially pathogenic Aeromonas sobria from fish silver carp ( Hypophthalmichthys molitrix ). Assessment of clinical, microbiological, pathological and biochemical characteristics of A. sobria were taken into account in order to understand the epidemiology, frequency and occurrence of this infection. Clinically the infected fish (H. molitrix) was observed for various types of symptoms. A total of 33 colonies of A. sobria strain were isolated from 20 cultured H. molitrix, collected from controlled fish pond. Microscopic examination revealed that the strains were rod-shaped, Gram negative bacteria. The revealed percent probability identification of A. sobria from the biochemical characterization in VITEK system was 93% with gram negative (GN) card. The histopathology of Gills caused by this bacterium, A. sobria indicate haemorrhagic gill epithelia and epithelial hyperplasia. Lamelar epithelial hypertrophy and hyperplasia with degenerative changes of the epithelium and hypertrophic epitheliocystis infected cells on gills of H. molitrix were observed during the present study.